Exposing tech skills shaping mobile learning in cross-disciplinary English learners - Vega, Nofvia De; Basri, Muhammad; Nur, Sahril (Intelektual Pustaka Media Utama, 2025)
This study delves into information and communication technology (ICT) competency and mobile learning (m-learning) acceptance among Indonesian university students enrolled in English for specific purposes (ESP) programs across various disciplines, such as mathematics, health, management, and counselling guidance. Utilizing survey methodology with closed-ended questions involving a broad sample of non-English major ESP students from these diverse fields revealed over 60% competency in using m-learning platforms. The results underscore the extensive use of digital technology across campus for diverse functions like communication, creation, distribution, storage, and management. These tools have proven crucial for collaboration and social interaction among students. However, pedagogical factors significantly challenge m-learning adoption. This study contributes to the literature by offering insights into ICT competencies' impact on m-learning acceptance among cross-disciplinary ESP learners. The findings carry practical implications for educators, suggesting that understanding ICT competencies can enhance student outcomes and engagement in m-learning platforms. Future research is recommended to incorporate perspectives from students and lecturers on the influence of ICT competencies on m-learning acceptance in cross-disciplinary ESP programs.